Negative effects of mobbing on work performance and efficiency of personnel working in public and private medical institutions, an applied Turkey example - Korkmaz, Murat; Kiliç, Bülent; Yücel, Ali Serdar; Gümüşda?, Hayrettin; Aksoy, Muzaffer (American-Eurasian Network for Scientific Information, 2014)
The purpose of this study is to examine the negative effects of mobbing on work performance and efficiency, which is implemented on the personnel working in public and private medical institutions. A total of 2500 employees working in different branches of public and private medical institutions in Istanbul participated in the research. A two-part questionnaire was prepared for the participants. Data obtained from the research were put through reliability test and Cronbach Alpha coefficient was found 0.99. Data obtained were evaluated with t-test and one-way variance analysis, and significant differences were found with tukey test. Following the research, it has been concluded that mobbing affects the participants' health negatively and this effect differentiates according to the demographic characteristics. Moreover, it has been found that mobbing has a negative effect on work performance and efficiency of the participants and this effect differs again according to the demographic characteristics. © 2014 AENSI Publisher All rights reserved.
Keywords: Efficiency; Medical institution; Mobbing; Work performance